Equine cheek tooth extraction: Comparison of outcomes for five extraction methods. (30th July 2019) - Caramello, V.; Zarucco, L.; Foster, D.; Boston, R.; Stefanovski, D.; Orsini, J. A.
Summary: Background: Post‐operative complications are reported for all methods of equine cheek tooth extraction but not all methods carry the same risks. An outcome comparison for commonly used methods is needed so that clinicians can make informed treatment decisions. Objectives: We conducted a side‐by‐side comparison of five cheek tooth extraction methods, comparing types and incidence of complications among oral extraction, tooth repulsion (three surgical approaches) and lateral buccotomy techniques. Study design: Retrospective clinical study using hospital medical records. Methods: Medical records of all horses undergoing cheek tooth extraction between 1997 and 2013 were reviewed. Logistic regression was used to determine the likelihood of various post‐operative complications, comparing oral extraction, tooth repulsion by maxillary and mandibular trephination or maxillary sinus bone flap, and lateral buccotomy. Results: The study included 137 horses and 162 cheek teeth extractions. Oral extraction was successful in 71% of patients in which it was attempted. Oral extraction (n = 55) had the lowest incidence of complications (20%) and repulsion by sinus bone flap (n = 20) the highest (80%). Complication rates for repulsion by maxillary (n = 19) and mandibular trephination (n = 28), and extraction by lateral buccotomy (n = 15) were 42, 54 and 53%, respectively. Cheek tooth repulsion by sinus bone flap significantly increased the odds of damage to adjacent teeth, post‐operative sinusitis, damage to alveolar bone, delayed alveolar granulation and orosinus fistulation. Repulsion by maxillary trephination significantly increased the odds of superficial incisional surgical site infection; and extraction by lateral buccotomy significantly increased the odds of facial nerve neuropraxia. Post‐operative pyrexia was more common in all repulsion methods. Main limitations: Some clinically relevant differences may have been missed due to small group numbers in several categories. Conclusions: Oral extraction was associated with fewer post‐operative complications than any other methods. Standing oral extraction remains the preferred choice, and recent surgical advances promise to further improve its success rate.